PANORAMA OF ORTHODONTICS AFTER COVID-19: A CRITICAL LITERATURE REVIEW (SciELO Preprints, 2020)
A new Coronavirus (2019-nCov, renamed SARS-CoV-2) was identified in the Chinese city of Wuhan in late 2019, and was declared a pandemic by the World Health Organization, on March 11, 2020. As it is a highly infectious disease, major regional and national changes have been made, social isolation was recommended, which led to the interruption of various services, including elective dental treatments. This review aimed to identify the changes that occurred in the post-COVID-19 orthodontic practice scenario. For such, a search was made for articles published in the bibliographic bases PubMed, Scopus and SciELO, using the keywords “Orthodontics” and “Covid-19”. From the eligibility criteria, 11 articles were selected for analysis. It was found that social isolation impacted the scheduling of orthodontic appointments and patient’s anxiety about the duration of treatments. The use of teleodontology proved to be an ally in screening and in patient care. Preventive infection control must be adopted for safe orthodontic practice.